2007
DOI: 10.1177/039463200702000211
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase Isozymes in Oral Squamous Cell Carcinoma: A Real-Time RT-PCR Study with Clinic Pathological Correlations

Abstract: COX-2 expression in tumour cells has been associated with carcinogenesis in many human neoplasms, including head and neck cancer, while the COX-l isoform of the cyclooxygenase enzyme is constitutively expressed in normal tissues. We measured COX-l and COX-2 m-RNA expression in samples of both oral cancer and matched oral mucosa from 22 patients by RealTime RT-PCR; clinic pathological data (grading, TNM staging, inflammation, follow-up) of all patients were available for statistical evaluation. Most of the tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 15 publications
(13 reference statements)
1
41
1
Order By: Relevance
“…Our data are in agreement with all the studies [4,5,7,[23][24] that report a higher expression of COX-2 in precancerous lesions than in malignancies and that hypothesize a correlation between COX-2 activation and the early stages of carcinogenesis.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Our data are in agreement with all the studies [4,5,7,[23][24] that report a higher expression of COX-2 in precancerous lesions than in malignancies and that hypothesize a correlation between COX-2 activation and the early stages of carcinogenesis.…”
Section: Discussionsupporting
confidence: 94%
“…Moreover, opinions regarding the correlation between COX-2 expression and the histologic grade of oral cancer are highly conflicting; many authors report a progressive increase of COX-2 expression from normal oral mucosa towards invasive carcinoma [39,[41][42][43], others report an higher COX-2 expression in premalignant lesion than in malignancies [4,6,[44][45], while others report the lack of correlation between COX-2 level and tumor stage or grade [7,46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resection samples from 90 eligible mobile tongue SCC patients (47 males, 43 females) were analysed using a set of possible new and previously proposed immunohistochemical prognostic markers including microvessel density (CD31 and factor VIII), cyclooxygenase-2 (COX-2), the laminin-5 g2-chain, integrin avb6 and matrix metalloproteinases . The high expression levels of COX-2 are known to be associated with poor disease-free survival in oral squamous cell carcinoma (Pannone et al, 2007) and also laminin-5 g2-chain, a basement membrane protein (Gasparoni et al, 2007), and avb6 integrin, a transmembrane adhesion protein (Hynes, 1992) are known to be increased in invasive SCCs (Breuss et al, 1995;Jones et al, 1997;Ramos et al, 1997). Angiogenesis is crucial for tumour growth (Folkman et al, 1963) and metastasis (Folkman, 1990) but the role of angiogenesis is still controversial in oral SCC (Gasparini et al, 1993;Leedy et al, 1994;Hogmo et al, 1999;Macluskey et al, 2000) and thus deserves further investigation.…”
mentioning
confidence: 99%
“…Pannone et al demonstrated in 22 patients with OSCC via real-time RT-PCR that a high COX-2 expression was associated with a worse DFS. A correlation with QS, tumor stage and grade could not be shown [85]. At this time, studies analyzing the relation of HPV status, COX-2 expression and clinicopathological parameters in OSCC still have not been done.…”
Section: Cox-2mentioning
confidence: 94%